How perceived risk of recurrence strengthens health management awareness in stroke patients: the chain mediating role of risk fear and health literacy - Rong Lei; Ming Zhang; Gui Gui; Gui Gui; Dajun Yang; Dajun Yang; Dajun Yang; Linli He (Frontiers in Public Health)
BackgroundPrior research has found that perceived risk in stroke patients motivates health behaviors in visitors. However, the role that perceived risk of recurrence in stroke patients plays in reinforcing health management awareness during the motivation phase is unclear.ObjectiveThis study explores this issue by examining the effects of risk fear and health literacy on health management awareness due to perceived risk of recurrence in stroke patients.MethodsWe validated the effect of perceived risk of recurrence on health management awareness and its internal mechanism by constructing a structural equation model and including 763 stroke patients, extending the relevant literature and application of the Healthy Behavior Procedural Approach (HAPA) model.ResultThe results suggest that perceived risk of recurrence in stroke patients can effectively reinforce and improve health management awareness, with risk fear and health literacy having a chain-mediated role in this group relationship.ConclusionThis study reveals the differential effects of perceived risk of recurrence, risk fear, and health literacy in stroke patients on health management awareness at the individual level, providing valuable guidance for healthcare practitioners and families to improve patients’ health outcomes and health well-being.